Elevated temperature and nitrogen deposition did not affect the impacts of arbuscular mycorrhizal fungi on soil carbon or nitrogen stocks in atemperate meadow. (November 2021) - Cui, Nan; Zhao, Yinan; Sun, Fengwei; Wang, Mingming; Guo, Jixun; Shi, Lianxuan; Sun, Wei; Zhang, Tao
Highlights: Arbuscular mycorrhizal fungi reduced soil carbon (C) and nitrogen (N) stocks. Neither elevated temperature nor N deposition alter the response of soil C and N stocks to AM fungi. AM fungi can mitigate the negative effect of increasing N accumulation on ecosystem stability. Abstract: Arbuscular mycorrhizal (AM) fungi are key players in the soil carbon (C) and nitrogen (N) cycles; on the one hand, AM fungi have been influenced by global changes, while on the other hand, they are involved in shaping the future climate. However, few field studies have combined AM fungi with both elevated temperatures and N deposition to examine their potential combined effects on the stocks of soil C and N in temperate meadow ecosystems. A 5-year experiment was conducted to explore the effects of AM fungal reductions on soil C and N stocks under elevated temperatures and N deposition. The stock of soil C and N and the C:N ratio were measured. The results showed that AM fungi significantly reduced soil C stocks by 8.5% across all treatment combinations compared to the AM fungi suppression treatment, and slight soil C accumulation was detected across the five years. The response of the soil C stocks was not influenced by elevated temperatures and N deposition simultaneously. The soil N stocks in the treatments without AM fungal suppression were, on average, 9.7% lower across all treatments than those in the AM fungal suppression treatment. AM fungi, elevated temperatures, and N deposition did not affect the soil C:N ratio. The robust decreases in soil C and N stocks caused by AM fungi observed here, even when combined with other global changes, suggest that AM fungi might accelerate soil C losses in temperate meadow ecosystems; however, there is a strong potential for reduced soil N accumulations to mitigate the negative impact of increasing N deposition on the stability of grassland ecosystems under future global changes. Overall, our results highlight that the effect of AM fungi on soil C and N stocks has a high resistance to global warming and N deposition in temperate meadow ecosystems.